Motion management during SBRT for oligometastatic cancer: Results of a prospective phase II trial. Issue 3 (June 2016) - Van den Begin, Robbe; Engels, Benedikt; Boussaer, Marlies; Dhont, Jennifer; Burghelea, Manuela; Depuydt, Tom; Poels, Kenneth; Collen, Christine; Gevaert, Thierry; Verellen, Dirk; Storme, Guy; de Mey, Johan; et al.
Abstract: Purpose: To optimize the local control of stereotactic body radiotherapy (SBRT) using the Vero-SBRT system and respiratory motion management in patients with oligometastatic cancer. Materials and methods: Patients with five or less metastases were eligible. In metastases with significant motion, a fiducial was implanted for Vero dynamic tracking. For other metastases an internal target volume (ITV) was defined to encompass the respiratory tumor trajectory. A dose of 50 Gy in 10 fractions was prescribed on the 80% isodose line. Results: We treated 87 metastases in 44 patients, with colorectal cancer as the most common primary origin (65.9%). Metastatic sites were mainly lung ( n  = 62) and liver ( n  = 17). Twenty-seven metastases were treated with dynamic tracking, the remaining 60 using the ITV-concept. Three patients (7%) experienced grade ⩾3 toxicity. After a median follow-up of 12 months, the overall one-year local control (LC) amounted to 89% (95% CI 77–95%), with corresponding values of 90% and 88% for the metastases irradiated with the ITV-approach and dynamic tracking, respectively. Median progression-free survival reached 6.5 months, one-year overall survival 95%. Conclusions: SBRT with proper respiratory motion management resulted in a high LC and an acceptable toxicity profile in oligometastatic cancer patients.